Effectiveness of Budget Provisions to Promote Sustainable Forestry in Forest Reserves of Osun State, Nigeria - T.E, Olatunji (Asian Journal of Empirical Research, 2013)
Budget is a vital tool for government planning and control especially in the use and maintenance of natural resources like forests. Forestry production requires adequate funding which can only be obtained through budget appropriation process. The objective of this paper is to evaluate the extent to which annual budgetary provisions foster sustainable forestry in Osunstate. Budget provisions for revenue and expenditure were juxtaposed and their relativity shown. Actual expenditure was matched against the budgets to identify accounting variances. The ANOVA method was employed to analyze the data while the F- statistic was employed to test the significance of differences in the variables. Results show that budgetary provisions were inadequate and even that was hardly disbursed fully. There is a significant relationship between budgets and sustainable developments of forests in Osunstate. Budgets should reflect sustainable development ideals and be properly implemented.